THE ROLE OF SELF-REGULATION SKILLS IN LINKING GROWTH MINDSET AND LONELINESS TO PSYCHOLOGICAL WELLBEING AMONG MEDICAL STUDENTS (The Research of Medical Science Review, 2025)
Objectives: This study aimed to (1) examine the relationship of growth mindset and stress with psychological wellbeing among medical students, (2) assess the mediating role of self-regulation skills in this relationship, and (3) evaluate the combined influence of growth mindset and stress on psychological wellbeing through self-regulation skills.Methods: A quantitative, correlational research design was employed. Data were collected from 374 medical students through a self-administered online questionnaire. The study utilized standardized instruments: Growth Mindset Scale, Perceived Stress Scale, Self-Regulation Questionnaire–Short Version, and the Ryff Psychological Wellbeing Scale. SPSS version 25 was used to perform descriptive statistics, Pearson correlations, mediation analysis (using Hayes' PROCESS macro), and multiple regression analysis.Results: Growth mindset was positively correlated with psychological wellbeing (r = .47, p < .01) and negatively correlated with stress (r = –.38, p < .01). Stress was inversely related to wellbeing (r = –.43, p < .01). Mediation analysis confirmed that self-regulation partially mediated the relationships between both growth mindset and stress with psychological wellbeing. Multiple regression analysis revealed that growth mindset (β = .30), stress (β = –.31), and self-regulation (β = .34) significantly predicted psychological wellbeing (R² = .54, p < .001).Conclusion: The findings highlight self-regulation skills as a critical psychological mechanism that buffers the negative effects of stress and enhances the positive influence of growth mindset on mental wellbeing. Targeted interventions focusing on mindset and behavioral self-regulation may support emotional resilience and promote mental health in medical education.